2019
DOI: 10.3390/nu11091981
|View full text |Cite
|
Sign up to set email alerts
|

High-dose Glycerol Monolaurate Up-Regulated Beneficial Indigenous Microbiota without Inducing Metabolic Dysfunction and Systemic Inflammation: New Insights into Its Antimicrobial Potential

Abstract: Glycerol monolaurate (GML) has potent antimicrobial and anti-inflammatory activities. The present study aimed to assess the dose-dependent antimicrobial-effects of GML on the gut microbiota, glucose and lipid metabolism and inflammatory response in C57BL/6 mice. Mice were fed on diets supplemented with GML at dose of 400, 800 and 1600 mg kg−1 for 4 months, respectively. Results showed that supplementation of GML, regardless of the dosages, induced modest body weight gain without affecting epididymal/brown fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 56 publications
9
48
0
Order By: Relevance
“…Furthermore, increased SCFAs may improve the intestinal health and may assist the host in maintaining mucosal barrier integrity [ 70 , 72 ]. Mo, et al [ 73 ] showed that dietary GML improved the intestinal integrity and gut barrier function in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased SCFAs may improve the intestinal health and may assist the host in maintaining mucosal barrier integrity [ 70 , 72 ]. Mo, et al [ 73 ] showed that dietary GML improved the intestinal integrity and gut barrier function in mice.…”
Section: Discussionmentioning
confidence: 99%
“…GML had the strongest antimicrobial capacity among the medium chain 1-monoglycerides (MGs) and possess a broad antibacterial spectrum, especially in suppressing the growth of gram-positive bacteria in vitro [11]. Dietary GML in the diet of mice significantly altered the composition, microbial metabolite and function of gut microbiota, which consequently affected the animal performance and nutrients utilization [41,42]. The present study revealed that the gut microbiota composition and function were altered by GML supplementation, but their relationship with laying performance and feed efficiency required further study.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, we found that a higher dose of GML (1,600 mg/kg) significantly decreased chronic systemic inflammation and modulated gut microbiota in LFD-fed mice (21). In the present study, we examined the effects of 1,600 mg/kg GML supplementation on physiology and gut microbiota in HFD-fed mice.…”
mentioning
confidence: 82%